Accelerating diffusion innovation using celebrities as opinion leaders for millennials: HPV vaccines in Indonesia - Pinariya, Janette Maria; Ikhsano, Andre; Sutjipto, Aldila Maharani (Penerbit Universiti Kebangsaan Malaysia, 2020)
Indonesia has become the country with the second-highest number of cervical cancer patients. It is the only type of cancer that could be prevented, but the public's understanding is still very low. The urgency of this issue especially applied for the millennial generation. This study discusses the campaigns in the health sector conducted by Indonesia Cervical Cancer Prevention Coalition as an effort to introduce HPV vaccination as primary prevention of cervical cancer, where one of the main strategies used is by maximizing the role of celebrities as opinion leaders. This paper discusses how cervical cancer preventive measures are often seen as sensitive, frightening, and embarrassing by the millennial generation in Indonesia. Aims to obtain information about the use of celebrity opinion leaders as one of the KICKS communication strategies, obstacles faced and how to deal with them. The authors use a qualitative approach, with primary data obtained through interviews with seven informants. By using diffusion of innovation theory approach from Everett M. Rogers, which focuses on the role of opinion leaders, the results of this study show that what is done and said by opinion leaders regarding an innovation can be an important consideration for millennials. Where similarities that celebrities had as a part of the social system help making the message more relevant, memorable, reliable and trustworthy. However, it could not be denied that the use of celebrities as opinion leaders has its advantages and disadvantages, and besides that interpersonal communication is still needed.